Economic Regionalism in East Asia: Strengthening Regional Economic Cooperation for Economic Growth and Financial Stability - Lee, Yu-Ra (Université d'Ottawa | University of Ottawa, 2013)
Regionalism has emerged as an important world-wide feature of the global economy along with multilateralism. As EU and NAFTA have shown, the integration of economic activities within particular regions has been intensified. Compared to Europe and North America, East Asia has shown relatively slow progress towards the global trend of regionalism. The Asian financial crisis of 1997-1998 was a strong impetus for initiating a trend toward regionalism in East Asia. In the aftermath of the financial crisis, East Asian countries have come to realize the necessity for regional economic cooperation mechanism for preventing, managing, and resolving economic crises, as well as for increasing trade and investment, and promoting sustainable economic growth and financial stability in the region. This research paper assesses the current progress of regional economic cooperation in East Asia by focusing on the area of trade and finance. In addition, this paper provides policy suggestions and a road map to enhance the effectiveness of economic cooperation in East Asia.